Analysis of Road Accidents using Machine Learning - G Pavan Karthik, Sneha B, Sudalaimuthu T (International Journal of Advanced Science and Technology, 2020)
With the world-class medical facilities, the infant mortality rate has plummeted sharply, and the life expectancy has surged. The eradication of diseases like Polio, Smallpox proves the advancement of humans and the betterment of our lives. Amidst all these, one uncertainty has not been yet eliminated fully that the Road accidents would save millions of lives every year, and the emphasis on this has been the top priority. The road accidents have to be minimized t reduce the deaths by accidents. In total, 4, 67,700 accidents happened last year in India, 1, 51,427 people were died.  A simple calculation tells us that every passing hour in India, 53 accidents occur and 17 die in a road accident. These ghastly numbers and statistics, coupled with the possibility of creating a tool using Machine Learning, are the primary motivational factors for choosing this project.Keywords–Machine Learning (ML), Data  Mining  (DM), Fatal Analysis Reporting System(FARS), Neural Networks (NN), Support Vector Machines (SVM).